Ultrafine ground calcium carbonate with high specific surface area and low moisture content for sealant as well as preparation method and application of ultrafine ground calcium carbonate

Ultrafine heavy calcium carbonate with high specific surface area and low moisture was prepared through wet grinding and multiple grading techniques, which solved the problems of poor reinforcement effect and high moisture content of heavy calcium carbonate, improved the anti-settlement effect, and was suitable for sealing adhesive systems. , broadens the scope of application and reduces resource waste.

CN119192878APending Publication Date: 2024-12-27JIANGXI GUANGYUAN CHEM +1
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411340038.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The specific surface area of ​​heavy calcium carbonate in existing sealants is small and the moisture content is high, resulting in poor reinforcement effect, easy settlement and waste of resources, especially in two-component sealant systems that have poor anti-segmentation effect.

Method used

Wet grinding and multiple grading techniques were used to prepare ultrafine heavy calcium carbonate, wet grinding was performed by mixing calcite particles and compound grinding additives, followed by multiple grading and water removal modification, and the particle diameter was controlled to be ≤2μm and the ratio was The surface area is ≥9m2/g and the moisture is ≤500ppm, which improves the fineness of the powder and anti-settlement effect.

Benefits of technology

The preparation of high specific surface area and low moisture sealant is achieved, which improves powder fineness and anti-sealing effect, broadens the application range, and reduces resource waste. It is suitable for single-component and two-component sealant systems.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005059422360000061
    Figure BDA0005059422360000061
  • Figure BDA0005059422360000071
    Figure BDA0005059422360000071
  • Figure BDA0005059422360000081
    Figure BDA0005059422360000081
Patent Text Reader

Abstract

The invention relates to the technical field of fine chemical engineering, in particular to superfine ground calcium carbonate for a high-specific-surface-area low-moisture sealant as well as a preparation method and application of the superfine ground calcium carbonate. The preparation method comprises the following steps: mixing calcite particles with a compound grinding aid, and carrying out wet grinding to obtain a ground product; performing multiple grading treatment on the ground product to obtain a graded product; mixing the graded product with a moisture scavenger and a modifier, and modifying to obtain superfine heavy calcium carbonate; in the superfine heavy calcium carbonate, the content of particles smaller than or equal to 2 microns in calcium carbonate is larger than or equal to 85 wt%, D97 is smaller than or equal to 2.7 microns, the specific surface area is larger than or equal to 9 m < 2 > / g, and the water content is smaller than or equal to 500 ppm, the problems that traditional heavy calcium carbonate is poor in reinforcing effect, relatively high in water content and prone to sedimentation are solved, the dehydration time can be saved, the production efficiency can be improved, and the requirements of downstream customers are met; meanwhile, the stability of batches is good, the anti-settling effect is good, and part of light nano-calcium can be replaced in sealant production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of fine chemical industry, and in particular relates to ultrafine heavy calcium carbonate for high specific surface area and low moisture sealant, and a preparation method and application thereof. Background Art

[0002] In daily life, sealant products are often used when encountering problems such as leak prevention, waterproofing, vibration prevention, sound insulation, and heat insulation. For sealants, except for some transparent or special application sealants, a large part of their formula system is inorganic fillers, generally accounting for more than 50%. The most common are light nano calcium and heavy calcium carbonate. Light nano calcium plays a role in improving rheological properties, reinforcement, and filling, while heavy calcium carbonate mainly plays a role in regulating viscosity and volume filling. The main components of light nano calcium and heavy calcium carbonate are calcium carbonate. The difference in their properties mainly lies in the different production processes. Light nano calcium is produced by chemical methods. Its general production process includes calcination, digestion, carbonization, surface modification, filtration, drying, and breaking up, which are accompanied by chemical reaction processes. Its product characteristics are small powder particle size, large specific surface area, and relatively regular morphology (spherical, cubic, spindle-shaped, etc.). The disadvantage is high energy consumption and easy fluctuations between product batches. Heavy calcium carbonate (hereinafter referred to as heavy calcium carbonate) is prepared by physical grinding, which involves washing and crushing the ore and grinding it directly. Its raw materials are widely available, non-toxic and environmentally friendly, and are widely used in building materials, metallurgy, papermaking, chemical industry and other fields. The most common products are 1250 mesh and below, with a specific surface area of ​​​​≤4m 2 / g,D 97 ≥10μm, widely used to fill paint, adhesive, rubber, plastic, ink and other polymer systems, mainly for volume filling, with limited effect on improving colloid performance, especially in two-component sealant system (resin system and curing system), due to poor anti-settling effect, long-term non-use is prone to stratification. In addition, the added value is low, which is easy to cause waste of resources.

[0003] In addition, the single-component curing mechanism of the currently common silicone, polyurethane, polysulfide and other sealants is mostly to absorb moisture in the air to cure. Therefore, in order to extend the storage period of single-component sealants, manufacturers will make certain requirements on the moisture content in the raw materials used in production. The lower the moisture content, the better. This is because high moisture content will increase the viscosity of the colloid during the production process, making it more difficult for the powder to settle. Summary of the invention

[0004] The purpose of the present invention is to provide an ultrafine heavy calcium carbonate for high specific surface area and low moisture sealant and a preparation method and application thereof. The heavy calcium carbonate has a moisture content of ≤500ppm, good anti-settling effect, and is suitable for single-component and two-component systems.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The present invention provides a method for preparing ultrafine heavy calcium carbonate for high specific surface area and low moisture sealant, comprising the following steps:

[0007] The calcite particles are mixed with a compound grinding aid and wet-grinded to obtain a grinding product;

[0008] The ground product is subjected to multiple classification processes to obtain a classified product;

[0009] The classified product is mixed with a dehydrating agent and a modifier to perform modification to obtain ultrafine heavy calcium carbonate;

[0010] The content of particles ≤2 μm in the ultrafine heavy calcium carbonate is ≥85wt%, D 97 ≤2.7μm, specific surface area ≥9m 2 / g, moisture content ≤500ppm.

[0011] Preferably, the particle size of the calcite particles is 2-3 mm, the calcium carbonate content in the calcite is ≥97%, the magnesium carbonate content is ≤2%, and the quartz content is ≤0.2%.

[0012] Preferably, the compound grinding aid includes stearic acid, decanoic acid, ethylene glycol and water, the mass of the compound grinding aid is 1 to 3‰ of the mass of the calcite particles, and the mass ratio of stearic acid, decanoic acid, ethylene glycol and water is 2 to 4:1 to 3:2:3.

[0013] Preferably, the inner lining of the ball mill used for the wet grinding is alumina ceramics, and the grinding medium is alumina balls.

[0014] Preferably, the multiple classification processes include a first classification, a second classification and a third classification performed in sequence; the rotation speed of the classifier used in the first classification is 1200-1500 r / min, and the rotation speeds of the classifiers used in the second classification and the third classification are independently 2800-3200 r / min.

[0015] Preferably, the content of particles ≤2 μm in the classified product is ≥85wt%, D 97 ≤1.9μm, specific surface area ≥9m 2 / g.

[0016] Preferably, the dewatering agent is quicklime, and the mass of the dewatering agent is 1-3‰ of the calcite particles; the modifier is stearic acid, and the mass of the modifier is 6-10‰ of the calcite particles.

[0017] Preferably, the modification is carried out in a high-speed mixer at a temperature of 140 to 160° C., a time of 10 to 15 min, and a rotation speed of 1200 to 1600 r / min.

[0018] The present invention provides ultrafine heavy calcium carbonate for high specific surface area and low moisture sealant prepared by the preparation method described in the above technical scheme.

[0019] The present invention provides the use of the ultrafine heavy calcium carbonate for high specific surface area and low moisture sealant described in the above technical solution in the sealant.

[0020] Beneficial effects of the present invention:

[0021] The invention adopts wet grinding technology, effectively avoiding the entry of magnetic impurities such as iron filings during the grinding process, reducing the dielectric constant of the powder, so that it can be used in the fields of electronic glue, electronic potting glue, etc., broadening the application range; adopting multiple classification technology, it can directly separate particles with a diameter of ≤2μm and a content of ≥85wt%, D 97 ≤2.7μm, specific surface area ≥9m 2 / g product, good batch stability, improved product powder fineness, enhanced anti-sedimentation effect, can replace part of lightweight nano calcium in sealant production. The present invention solves the problem of poor reinforcement effect and easy sedimentation of traditional heavy calcium by controlling the particle size of heavy calcium powder (the traditional heavy calcium has low fineness, and the content of particles with a diameter of ≤2μm is generally less than 30%, and the common content is about 20%, and the specific surface area is ≤3m 2 / g).

[0022] Furthermore, the present invention adopts high-temperature and high-speed dispersion to realize water removal and surface modification in a one-step process. The high temperature in the high-speed mixer is used to remove most of the water first, and then a water removal agent is added to remove the residual water, and then a modifier is added to perform surface modification treatment, which can effectively remove the water in the system. The water content of the prepared product is ≤500ppm, which can save dehydration time, improve production efficiency, meet the needs of downstream customers, and solve the problem of relatively high water content in traditional calcium carbonate fillers (the water content in traditional calcium carbonate (containing light calcium and heavy calcium) is generally around 2000ppm). DETAILED DESCRIPTION

[0023] The present invention provides a method for preparing ultrafine heavy calcium carbonate for high specific surface area and low moisture sealant, comprising the following steps:

[0024] The calcite particles are mixed with a compound grinding aid and wet-grinded to obtain a grinding product;

[0025] The ground product is subjected to multiple classification processes to obtain a classified product;

[0026] The classified product is mixed with a dehydrating agent and a modifier to perform modification to obtain ultrafine heavy calcium carbonate;

[0027] The content of particles ≤2 μm in the ultrafine heavy calcium carbonate is ≥85wt%, D 97 ≤2.7μm, specific surface area ≥9m 2 / g, moisture content ≤500ppm.

[0028] In the present invention, the calcite particles are preferably prepared by washing natural ore and feeding it into a jaw crusher and a rotary cone crusher in turn, and the crushed materials are screened by a linear vibrating screen; the calcite particles are preferably homogenized and stored in a large storage tank; the particle size of the calcite particles is preferably 2 to 3 mm, the calcium carbonate content in the calcite is preferably ≥97%, the magnesium carbonate content is preferably ≤2%, and the quartz content is preferably ≤0.2%.

[0029] In the present invention, the compound grinding aid preferably includes stearic acid, decanoic acid, ethylene glycol and water, the mass of the compound grinding aid is preferably 1-3‰ of the mass of the calcite particles, more preferably 2-3‰, the mass ratio of stearic acid, decanoic acid, ethylene glycol and water is preferably 2-4:1-3:2:3, more preferably 3-4:2-3:2:3, further preferably 4:3:2:3. The present invention uses a compound of stearic acid, decanoic acid, ethylene glycol and water as a functional grinding aid, and preliminarily coats the surface of calcium carbonate particles while grinding and dispersing, thereby changing the polarity of the surface layer of the particles and improving their compatibility with non-polar resins in downstream applications.

[0030] In the present invention, the ball mill used for the wet grinding is preferably a drum ball mill (Xuzhou Malone Energy Saving and Environmental Protection Equipment Co., Ltd.), the inner lining of the ball mill is preferably alumina ceramics, and the grinding medium is preferably alumina balls.

[0031] In the present invention, the multiple classification treatment preferably includes the first classification, the second classification and the third classification performed in sequence; the classifiers used in the multiple classification are preferably three horizontal vortex airflow classifiers connected in series; the speed of the classifier used in the first classification is preferably 1200-1500r / min, more preferably 1300-1400r / min, and the speed of the classifiers used in the second classification and the third classification is preferably 2800-3200r / min, more preferably 3000-3200r / min. The present invention adopts multiple classification to directly separate D 97 ≤2.7μm, specific surface area ≥9m 2 / g products have good batch stability, improved fineness and enhanced anti-sedimentation effect.

[0032] In the present invention, the classification is specifically as follows: the material ground by the drum ball mill is fed into three series-connected horizontal vortex airflow classifiers through a wind conveying system according to the flow rate for multiple classifications. Large particles have a slow speed and will be stopped by the fan blades, while small particles can pass through the fan blades to achieve a classification effect; the qualified heavy calcium particles are collected by a collector and stored in a storage tank, and the unqualified products are returned to the grinding equipment for re-grinding.

[0033] In the present invention, the content of particles ≤2 μm in the classified product is ≥85wt% and the specific surface area is ≥9m 2 / g.

[0034] In the present invention, the dewatering agent is preferably quicklime. Quicklime is used because quicklime CaO reacts with water and CO2 to generate calcium carbonate, which is consistent with the composition of filler calcite, and is cheap and easy to obtain; the mass of the dewatering agent is preferably 1-3‰ of the calcite particles, and more preferably 2-3‰; the modifier is preferably stearic acid, which is hydrophobic and can isolate water vapor after coating, effectively reducing the oil absorption value of the powder, and at the same time reducing the ability of the powder to absorb water vapor in the air, thereby reducing the moisture content in the heavy calcium carbonate; the mass of the modifier is preferably 6-10‰ of the calcite particles, and more preferably 6-8‰.

[0035] In the present invention, the modification is carried out in a high-speed mixer, the modification temperature is preferably 140-160°C, more preferably 150-160°C, the modification time is preferably 10-15min, more preferably 13-15min, the modification speed is preferably 1200-1600r / min, more preferably 1600r / min.

[0036] In the present invention, the graded product is preferably heated and dispersed at high speed, dehydrated and modified in a high-speed mixer; the graded product is preferably mixed with a dehydrating agent and a modifier by adding the graded product to a high-speed mixer and stirring for 10 to 15 minutes, adding a dehydrating agent, stirring for 5 minutes, adding a modifier, stirring for another 15 minutes, and cooling in a storage tank. The present invention adopts high-temperature and high-speed dispersion, and at the same time, adds a dehydrating agent before surface modification, which can effectively remove moisture from the system and meet the needs of downstream customers.

[0037] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0038] Example 1

[0039] Calcite (natural ore mined from mines, with a calcium carbonate content of 98.13%, a magnesium carbonate content of 0.76%, and a quartz content of 0.92%) was washed and crushed and then fed into a jaw crusher and a rotary cone crusher. The crushed material was screened by a linear vibrating screen to control the particle size of the calcite particles to 2-3 mm, and then homogenized and stored in a large storage tank. The homogenized material was then fed into a ball mill with an alumina ceramic lining and alumina balls as the grinding medium, and a composite grinding aid with a mass of 1‰ of the mass of the calcite particles was added, wherein the mass ratio of stearic acid, decanoic acid, ethylene glycol and water was 2:1:2:3, and the ground powder was repeatedly classified by three horizontal vortex airflow classifiers in series to obtain a fineness that met the requirements (≤2μm particle content ≥85wt%, specific surface area ≥9m 2 / g) of powder, wherein the speeds of the classifier are 1200r / min, 2800r / min, and 2800r / min respectively; preheating a high-speed mixer (the speed of the mixer is 1200r / min) to 150°C, adding the classified powder and stirring for 10min, adding quicklime with a mass of 1‰ of the mass of the calcite particles, stirring for 5min, then adding stearic acid with a mass of 6‰ of the mass of the calcite particles, stirring for 15min, collecting, cooling, and vacuum packaging in a film-coated packaging bag to obtain ultrafine heavy calcium carbonate for sealant with high specific surface area and low moisture content.

[0040] Five samples were randomly selected from the prepared products for inspection. The oil absorption value, particle size, sedimentation volume and specific surface area of ​​the products were measured based on the national standard GB / T 19281-2014, and the results were recorded in Table 1.

[0041] Table 1 Test results of heavy calcium prepared in Example 1

[0042]

[0043] As shown in Table 1, the 3h sedimentation volume of the five samples in the classified products ranged from 5.0 to 5.1 mL. After the product was classified, the sedimentation volume increased, the powder particles decreased, and the anti-sedimentation effect was improved. 97 In the range of 2.1-2.3 μm, the proportion of powders ≤2 μm is as high as 94.87 wt%, and the BET specific surface area is as high as 10.028 m 2 / g, moisture as low as 405ppm.

[0044] Example 2

[0045] Calcite (natural ore mined from mines, with a calcium carbonate content of 98.13%, a magnesium carbonate content of 0.76%, and a quartz content of 0.92%) was washed and crushed and then fed into a jaw crusher and a rotary cone crusher. The crushed material was screened by a linear vibrating screen to control the particle size of the calcite particles to 2-3 mm, and then homogenized and stored in a large storage tank. The homogenized material was then fed into a ball mill with an alumina ceramic lining and alumina balls as the grinding medium, and a composite grinding aid with a mass of 2‰ of the mass of the calcite particles was added, wherein the mass ratio of stearic acid, decanoic acid, ethylene glycol and water was 3:2:2:3, and the ground powder was repeatedly classified by three horizontal vortex airflow classifiers in series to obtain a fineness that met the requirements (≤2μm particle content ≥85wt%, specific surface area ≥9m 2 / g) of powder, wherein the rotating speeds of the classifier are 1300r / min, 3000r / min, and 3000r / min respectively; preheating a high-speed mixer (the rotating speed of the mixer is 1500r / min) to 150°C, adding the classified powder and stirring for 13min, adding quicklime with a mass of 2‰ of the mass of the calcite particles, stirring for 5min, then adding stearic acid with a mass of 8‰ of the mass of the calcite particles, stirring for 15min, collecting, cooling, and vacuum packaging in a film-coated packaging bag to obtain ultrafine heavy calcium carbonate for sealant with high specific surface area and low moisture content.

[0046] Five samples were randomly selected from the prepared products for inspection. The oil absorption value, particle size, sedimentation volume and specific surface area of ​​the products were measured based on the national standard GB / T 192812014, and the results were recorded in Table 2.

[0047] Table 2 Detection results of heavy calcium batch samples prepared in Example 2

[0048]

[0049] As shown in Table 2, the 3h sedimentation volume of the five samples in the classified product is 5.1 mL. After the product is classified, the sedimentation volume increases, the powder particles decrease, and the anti-sedimentation effect is improved. 97 In the range of 2.0-2.3 μm, the proportion of powders ≤ 2 μm is as high as 96.29 wt%, and the BET specific surface area is as high as 9.655 m 2 / g, moisture as low as 393ppm.

[0050] Example 3

[0051] Calcite (natural ore mined from mines, with a calcium carbonate content of 98.13%, a magnesium carbonate content of 0.76%, and a quartz content of 0.92%) was washed and crushed and then fed into a jaw crusher and a rotary cone crusher. The crushed material was screened by a linear vibrating screen to control the particle size of the calcite particles to be 2-3 mm. It was homogenized and stored in a large storage tank, and then the homogenized material was fed into a ball mill with an alumina ceramic lining and alumina balls as the grinding medium. A composite grinding aid with a mass of 3‰ of the mass of the calcite particles was added, wherein the mass ratio of stearic acid, decanoic acid, ethylene glycol and water was 4:3:2:3. The ground powder was classified multiple times by three horizontal vortex airflow classifiers in series to obtain a particle size that meets the requirements (≤2μm particle content ≥85wt%, specific surface area ≥9m 2 / g) of powder, wherein the speeds of the classifier are 1500r / min, 3200r / min, and 3200r / min respectively; preheating a high-speed mixer (the speed of the mixer is 1600r / min) to 150°C, adding the classified powder and stirring for 15 minutes, adding quicklime with a mass of 3‰ of the mass of the calcite particles, stirring for 5 minutes, then adding stearic acid with a mass of 8‰ of the mass of the calcite particles, stirring for 15 minutes, collecting, cooling, and vacuum packaging in a film-coated packaging bag to obtain ultrafine heavy calcium carbonate for sealant with high specific surface area and low moisture content.

[0052] Five samples were randomly selected from the prepared products for inspection. Based on the national standard GB / T 19281-2014, the oil absorption value, particle size, sedimentation volume and specific surface area of ​​the products were measured, and the results were recorded in Table 3.

[0053] Table 3 Heavy calcium test results prepared in Example 3

[0054]

[0055] As shown in Table 3, the 3h sedimentation volume of the five samples in the classified products ranged from 5.1 to 5.2 mL. After the product was classified, the sedimentation volume increased, the powder particles decreased, and the anti-sedimentation effect was improved. 97 In the range of 2.0-2.2μm, the proportion of powders ≤2μm is as high as 96.48wt%, and the BET specific surface area is as high as 10.133m 2 / g, moisture as low as 376ppm.

[0056] Comparative Example 1

[0057] Five samples of 800-mesh and 1200-mesh conventional heavy calcium were randomly selected for inspection. The sedimentation volume of the product was determined based on the national standard GB / T192812014, and the results are recorded in Table 4.

[0058] Table 4 Test results of conventional heavy calcium precipitation volume

[0059]

[0060] It can be seen from Table 4 that the 3-hour sedimentation volume of conventional heavy calcium with a particle size of 800 mesh is in the range of 1.2 to 1.3 mL, and the 3-hour sedimentation volume of conventional heavy calcium with a particle size of 1200 mesh is in the range of 1.5 to 1.6 mL.

[0061] From the comparison of Tables 1 to 4 above, it can be seen that the 3h sedimentation volume range of the heavy calcium carbonate obtained by the present invention is 5.0 to 5.2 mL, and the 3h sedimentation volume range of the existing heavy calcium carbonate in Comparative Example 1 is 1.2 to 1.6 mL, which indicates that the heavy calcium carbonate of the present invention has a significantly increased sedimentation volume and an enhanced anti-sedimentation effect compared with conventional heavy calcium carbonate; the present invention increases the sedimentation volume of heavy calcium carbonate by controlling the fineness of the powder, thereby improving the anti-sedimentation effect of heavy calcium carbonate.

[0062] From the above examples 1 to 3 and comparative example 1, it can be seen that the present invention provides an ultrafine heavy calcium carbonate for high specific surface area and low moisture sealant, wherein the content of particles ≤ 2 μm is ≥ 85 wt %, D 97 ≤2.7μm, specific surface area ≥9m 2 / g, moisture ≤500ppm; at the same time, heavy calcium has good batch stability and good anti-sedimentation effect, which solves the problems of poor reinforcement effect, relatively high moisture content and easy sedimentation of traditional heavy calcium.

[0063] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing ultrafine heavy calcium carbonate for high specific surface area and low moisture sealant, characterized in that: The following steps are involved: The calcite particles are mixed with a compound grinding aid and wet-grinded to obtain a grinding product; The ground product is subjected to multiple classification processes to obtain a classified product; The classified product is mixed with a dehydrating agent and a modifier to perform modification to obtain ultrafine heavy calcium carbonate; The content of particles ≤2 μm in the ultrafine heavy calcium carbonate is ≥85wt%, D 97 ≤2.7μm, specific surface area ≥9m 2 / g, moisture content ≤500ppm.

2. The preparation method according to claim 1, characterized in that: The particle size of the calcite particles is 2-3 mm, the calcium carbonate content in the calcite is ≥97%, the magnesium carbonate content is ≤2%, and the quartz content is ≤0.2%.

3. The preparation method according to claim 1, characterized in that: The compound grinding aid comprises stearic acid, decanoic acid, ethylene glycol and water. The mass of the compound grinding aid is 1-3‰ of the mass of the calcite particles. The mass ratio of stearic acid, decanoic acid, ethylene glycol and water is 2-4:1-3:2:

3.

4. The preparation method according to claim 1, characterized in that: The inner lining of the ball mill used for the wet grinding is alumina ceramics, and the grinding medium is alumina balls.

5. The preparation method according to claim 1, characterized in that: The multiple classification processes include first classification, second classification and third classification performed in sequence; the rotation speed of the classifier used in the first classification is 1200-1500 r / min, and the rotation speeds of the classifiers used in the second classification and the third classification are independently 2800-3200 r / min.

6. The preparation method according to claim 1, characterized in that: The content of particles ≤2 μm in the classified product is ≥85wt%, D 97 ≤1.9μm, specific surface area ≥9m 2 / g.

7. The preparation method according to claim 1, characterized in that: The dewatering agent is quicklime, and the mass of the dewatering agent is 1-3‰ of the calcite particles; the modifier is stearic acid, and the mass of the modifier is 6-10‰ of the calcite particles.

8. The preparation method according to claim 1, characterized in that: The modification is carried out in a high-speed mixer at a temperature of 140 to 160° C., a time of 10 to 15 minutes, and a rotation speed of 1200 to 1600 r / min.

9. Ultrafine heavy calcium carbonate for high specific surface area and low moisture sealant prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the ultrafine heavy calcium carbonate for high specific surface area and low moisture sealant according to claim 9 in sealant.

Citation Information

Cited By

  • Water-based stearic acid emulsion in-situ modified heavy calcium carbonate as well as preparation method and application thereof

    CN119978850A

  • Calcium-based carbonate compound, composition, molded plate, inorganic molded body, and method for producing calcium-based carbonate compound

    JP7809239B1